Empowering Housewives through Digital Branding on Social Media in Pasaran Island, Bandar Lampung - Yuniarti Fihartini; Dwi Asri Siti Ambarwati; Lis Andriani; Lidya Ayuni Putri; Siti Nurul 'ain Hj Zaiton (Universitas Teknokrat Indonesia, 2026)
Pasaran Island in Bandar Lampung City has high local economic potential through home-based small businesses, particularly in the seafood processing sector. However, most business owners have not yet utilized digital technology and social media optimally as tools for promotion and branding. The lack of digital literacy and limited understanding of digital branding strategies are the main challenges. Through this community service program, training and mentoring were provided to housewives as the primary actors of family-based MSMEs to strengthen their digital capacity, particularly in building business image and marketing through social media. This program aims to enhance the competitiveness of local products, expand market reach, and promote women's economic independence in coastal areas. The activities were designed in the form of technical training, digital branding education, practical management of business social media accounts, and evaluation of digital engagement outcomes.